2013
DOI: 10.1142/s2010135x1350032x
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric study of ferroelectric BaTiO3 in cubic phase

Abstract: Precise specific heat of barium titanate single crystals of different quality has been measured with special attention to the temperature region above the ferroelectric phase transition. It is shown that excess specific heat of the multiaxial barium titanate in the paraelectric phase has a fluctuation nature and its temperature dependence is in accordance with the theoretical predictions of Levanyuk theory for multiaxial ferroelectrics. In this study the first observation of fluctuation contribution to the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Moreover, the mode frequency and the half width of the LA mode of both crystals were indistinguishable from each other in the paraelectric phase. Grabovsky et al investigated the specific heat of several BaTiO 3 single crystals of different origin and found that the addition contribution to the specific heat exists in the paraelectric phase [57]. This anomalous high-temperature specific-heat existed up to T C + 60 K and was independent of the sample growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mode frequency and the half width of the LA mode of both crystals were indistinguishable from each other in the paraelectric phase. Grabovsky et al investigated the specific heat of several BaTiO 3 single crystals of different origin and found that the addition contribution to the specific heat exists in the paraelectric phase [57]. This anomalous high-temperature specific-heat existed up to T C + 60 K and was independent of the sample growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Let's now check this relationship for usefulness in practical application. For example, let us apply it to calculate the specific *e-mail: evgeniy.dulkin@mail.huji.ac.il heat, L, during the phase transition in BaTiO 3 crystals due to essential contradiction in their L values: ~ 2.37 J/kg 4 and ~ 0.54 J/kg 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The specific heat (C p ) shows a sharp and clear λ-type anomaly at T c in bulk BaTiO 3 [20]. In the case of thin films, it changes to a broad, small and characteristic one with decreasing film thickness [21].…”
Section: Introductionmentioning
confidence: 98%
“…Temperature dependence of specific heat of BaTiO 3 bulk single crystal around the paraelectric-ferroelectric phase transition point T c (409.5 K)[20]. Temperature dependence of specific heat of BaTiO 3 epitaxial thin films on SrTiO 3 substrate; (a) 2000 Å thick and (b) 60 Å thick[21].…”
mentioning
confidence: 99%